The maple leaf and the golden sun: A history of the Philippines-Canada relations, 1949-2019 - Chua, Ean Kevin Y. (Animo Repository, 2021)
The research traces the historical development of Philippines-Canada relations from its beginning in 1949 up to 2019. It discusses the interactions between the Philippine government and the Canadian government and how Philippine-Canadian ties progressed overtime. The researcher explores major areas that best constitute the high points of Philippines-Canada relations, such as political interactions, economic relations and social development. The study analyzes the diplomatic agreements, policies, treaties, aid and assistance, and other key features that are important in diplomatic relations. It also highlights major events in the history of Philippines-Canada ties, such as the establishment of the embassies between 1971 to 1972 and the waste dispute in 2013. The study is grounded on the conceptual framework of Smart Power introduced by Richard L. Armitage and Joseph S. Nye. This framework was used to explain the diplomatic strategies and policies utilized by the Philippine government and Canadian government to ensure growth and balance of bilateral ties. Furthermore, this study employed the descriptive, analytical, and narrative historical method based on M.C. Lemon’s Philosophy of History. Keywords: Philippine Diplomatic History; Foreign Relations; Philippine-Canadian Relations; Philippines-Canada Relations; Foreign Affairs